2016
DOI: 10.3390/ijerph14010034
|View full text |Cite
|
Sign up to set email alerts
|

Gold Mining in Ecuador: A Cross-Sectional Assessment of Mercury in Urine and Medical Symptoms in Miners from Portovelo/Zaruma

Abstract: Mercury is a toxic metal and is used in small scale gold mining. In Portovelo, Ecuador, mercury has been an environmental and health problem for decades. The target of this study was to assess the mercury concentration in the urine of miners from Portovelo/Zaruma to establish a prevalence of high values. Eight hundred and sixty-five (865) urine samples were collected and analysed for their mercury content, using cold vapor atom absorption spectroscopy. The prevalence of high mercury values (>25 μg/L) was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…For Cd in urine, the studies from Ghana, Spain and Guatemala showed very similar results [23,46,47]. The levels of Hg in urine found in our study are comparable to what has been found in other ASGM areas with known Hg use [48][49][50][51][52]. In areas without known or recent use of Hg for gold extraction, urinary Hg levels were considerably lower [45][46][47].…”
Section: 2supporting
confidence: 87%
“…For Cd in urine, the studies from Ghana, Spain and Guatemala showed very similar results [23,46,47]. The levels of Hg in urine found in our study are comparable to what has been found in other ASGM areas with known Hg use [48][49][50][51][52]. In areas without known or recent use of Hg for gold extraction, urinary Hg levels were considerably lower [45][46][47].…”
Section: 2supporting
confidence: 87%
“…In addition, the gold industry has caused environmental and health problems for decades to miners and mining communities. For example, there is an increasing concern for the health of miners and mining communities related to the mercury exposure, a toxic metal used in small-scale gold mining, and for the ecosystems' degradation due to mining land use [8,9]. Therefore, looking at the total mining costs, such as production costs, economic costs, environmental costs, and social costs, of these two assets or "safe havens", probably a wide spread of Bitcoin could allow us to better address the environmental aspects of sustainability and to have substantially higher savings than gold [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Some have been exploited for many decades or even centuries by ASGM. Well-known ASGM areas in Ecuador are Nambija, Zaruma-Portovelo and Ponce-Enríquez [ 26 , 27 , 28 , 29 , 30 , 31 ]. Other major deposits have been recently discovered and due to their characteristics need more industrialized exploitation techniques.…”
Section: Introductionmentioning
confidence: 99%